Pre-existing anti-HCoV-OC43 immunity influences the durability and cross-reactivity of humoral response to SARS-CoV-2 vaccination - Hu, Caiqin; Wang, Zheng; Ren, Li; Hao, Yanling; Zhu, Meiling; Jiang, He; Wang, Shuo; Li, Dan; Shao, Yiming (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose This study was conducted in order to properly understand whether prior seasonal human coronavirus (HCoV) immunity could impact the potential cross-reactivity of humoral responses induced by SARS-CoV-2 vaccine, thereby devising universal coronavirus vaccines for future outbreaks. Methods We performed enzyme-linked immunosorbent assay (ELISA) to quantify the immunoglobulin G (IgG) antibody levels to spike (S) protein and S1 subunit of HCoVs (HCoV-OC43, HCoV-HKU1, HCoV-NL63, and HCoV-229E), and ELISA [anti-RBD and anti-nucleoprotein (N)], chemiluminescence immunoassay assays (anti-RBD), pseudovirus neutralization test, and authentic viral neutralization test to detect the binding and neutralizing antibodies to SARS-CoV-2 in the vaccinees. Results We found that the antibody of seasonal HCoVs did exist before vaccination and could be boosted by SARS-CoV-2 vaccine. A further analysis demonstrated that the prior S and S1 IgG antibodies of HCoV-OC43 were positively correlated with anti-RBD and neutralization antibodies to SARS-CoV-2 at 12 and 24 weeks after the second vaccination, and the correlation is more statistically significant at 24 weeks. The persistent antibody levels of SARS-CoV-2 were observed in vaccinees with higher pre-existing HCoV-OC43 antibodies. Conclusion Our data indicate that inactivated SARS-CoV-2 vaccination may confer cross-protection against seasonal coronaviruses in most individuals, and more importantly, the pre-existing HCoV-OC43 antibody was associated with protective immunity to SARS-CoV-2, supporting the development of a pan-coronavirus vaccine.